Empreendedores negros em Cuiabá/MT : formação educacional e inserção no mercado de trabalho - Barreto, Caryna Paes (2017)
This study aims to identify the recurrent elements in the insertion of black entrepreneurs in the labor market, in Cuiabá / MT. The research subjects are 08 (eight) entrepreneurs, residents of Cuiabá / MT and Várzea Grande / MT, who have companies in the service sector, as well as describe the professional trajectory and their insertion in the labor market, verifying the schooling, identifying they had some entrepreneurial stimulus through formal education and analyzed the role of families and support networks in the professional trajectory of the interviewees. The methodology adopted was based on a qualitative, exploratory and descriptive approach, with the use of a semi-structured interview, as a data collection instrument. In Brazil, in the 1990s, there was a greater stimulus for business owners, due to the change in the economy, with a growth in entrepreneurship. As a theoretical reference of this research, Schumpeter (1947 and 1983), Dolan (2006), Baggio and Baggio (2014), Dornelas (2007 and 2005), Jaccoud and Beghin (2002), Hasenbalg (2005). Figueiredo (2004), Davies (2009), Oliveira, Porcaro and Araújo (1985), Assis e Lima (2014), among others. According to the National Household Sample Survey (PNAD), conducted by the IBGE in 2016, the rise of the black person as an entrepreneur occurred, about 50% of the total amount. In Mato Grosso, there is still no data on the presence of the black entrepreneur in the sectors, and the present proposal is unprecedented. It is noticed that there is still prejudice regarding the skin color, linked to the intelligence and dynamism of the people. The relevance of the research focuses on "giving voice" to these social actors, sometimes silenced historically in Brazil. The Negro has to overcome in every way to succeed, in a field totally dominated by white people. Formal education has an important role in the professional trajectory, for the success of the black entrepreneur, being the professional training a source of constant training, in the majority of interviewees.